Protostars and planets VI - Beuther, Henrik; Klessen, Ralf S.; Dullemond, Cornelis; Henning, Thomas (Space Science, 2014)
Intro -- Contents -- Scientific Advisory Committee and List of Collaborating Authors -- Preface -- Part I: Molecular Clouds and Star Formation -- Formation of Molecular Clouds and Global Conditions for Star Formation / C. L. Dobbs, M. R. Krumholz, J. Ballesteros-Paredes, A. D. Bolatto, Y. Fukui, M. Heyer, M.-M. Mac Low, E. C. Ostriker, and E. Vázquez-Semadeni -- From Filamentary Networks to Dense Cores in Molecular Clouds: Toward a New Paradigm for Star Formation / P. André, J. Di Francesco, D. Ward-Thompson, S.-I. Inutsuka, R. E. Pudritz, and J. Pineda -- The Origin and Universality of the Stellar Initial Mass Function / S. S. R. Offner, P. C. Clark, P. Hennebelle, N. Bastian, M. R. Bate, P. F. Hopkins, E. Moreaux, and A. P. Whitworth -- The Star Formation Rate of Molecular Clouds / P. Padoan, C. Federrath, G. Chabrier, N. J. Evans II, D. Johnstone, J. K. Jørgensen, C. F. McKee, and Å. Nordlund -- The Link Between Magnetic Fields and Cloud/Star Formation / H.-B. Li, A. Goodman, T. K. Sridharan, M. Houde, Z.-Y. Li, G. Novak, and K. S. Tang -- The Milky Way as a Star Formation Engine / S. Molinari, J. Bally, S. Glover, T. Moore, A. Noriega-Crespo, R. Plume, L. Testi, E. Vázquez-Semadeni, A. Zavagno, J.-P. Bernard, and P. Martin -- Massive Star Formation / J. C. Tan, M. T. Beltrán, P. Caselli, F. Fontani, A. Fuente, M. R. Krumholz, C. F. McKee, and A. Stolte -- The Earliest Stages of Star and Planet Formation: Core Collapse, and the Formation of Disks and Outflows / Z.-Y. Li, R. Banerjee, R. E. Pudritz, J. K. Jørgensen, H. Shang, R. Krasnopolsky, and A. Maury -- The Evolution of Protostars: Insights from Ten Years of Infrared Surveys with Spitzer and Herschel / M. M. Dunham, A. M. Stutz, L. E. Allen, N. J. Evans II, W. J. Fischer, S. T. Megeath,P. C. Myers, S. S. R. Offner, C. A. Poteet, J. J. Tobin, and E. I. Vorobyov.